Experimental anisakid infections in mice. Issue 5 (September 2015) - Vericimo, M.A.; Figueiredo, I.; Teixeira, G.A.P.B.; Clemente, S.C. São
Abstract Anisakidosis is a human parasitic disease caused by infections with members of the Anisakidae family. Accidental infection after fish intake affects the gastrointestinal tract as a consequence of mechanical damage caused by migrating larvae. Infections can also trigger allergies, hives, severe asthma or anaphylaxis with angioedema. Although mouse models of intraperitoneal antigenic stimulation exist, enabling immunological studies, few models using gastric introduction of live larvae are available for the study of immunological and gastrointestinal damage in mice. This study was designed to characterize serum reactivity against Anisakis spp. and Contracaecum spp. in Balb/c mice following orogastric inoculation and to assess gastrointestinal damage. These anisakid species were classified at the Universidade Federal Fluminense (UFF) School of Veterinary Medicine and materials for live larval inoculation were developed at the UFF Immunobiology laboratory. Live larvae were inoculated following injection with a NaCl solution. Blood samples were collected and sera screened for immunoglobulin (Ig)E and IgG anti-larva responses to both nematodes, specific for somatic and excretory/secretory antigens, by enzyme-linked immunosorbent assay (ELISA). The means of the optical densities were analysed using analysis of variance (ANOVA) with Tukey's post-hoc test and the general linear model. This analysis identified the presence of anti-IgG seroreactivity to both somatic and excretory/secretory Anisakis antigens in inoculated animals compared with controls (P< 0.001), and no gastric or intestinal damage was observed. These experiments demonstrated that introduction of live Contracaecum spp. into the gastrointestinal tract did not elicit serum sensitization in animals.